A method for preparing high crystalline oriented boron nitride fiber
By combining electric field-induced crystallization and slow crystallization technology, the crystal shape and size are regulated by using crystals, and an electric field is applied during the calcination process, the problem of low orientation of boron nitride fibers is solved, and boron nitride fibers with high orientation and high mechanical properties are achieved, which are suitable for applications in high-tech fields.
Patent Information
- Application Number
- CN202311133541.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-09-04
AI Technical Summary
The existing boron nitride fibers have low orientation, resulting in poor mechanical properties and cannot meet the application needs in high-tech fields.
The electric field-induced crystallization technology is combined with the slow crystallization technology. By controlling the concentration and volatility rate of the precursor solution in the electric field, the crystal morphology and size are regulated using seed crystals, and an electric field is applied during the calcination process to maintain the fiber orientation.
Boron nitride fibers with high orientation and high mechanical properties have smooth surfaces and few defects. They are suitable for aerospace, metallurgy, nuclear industry and other fields.
Smart Images

Figure CN117164365B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic fiber preparation, and in particular relates to a method for preparing high-crystalline oriented boron nitride fiber. Background Art
[0002] Boron nitride (BN) materials have the characteristics of high hardness, high wear resistance, high corrosion resistance and high temperature stability, and are widely used in high-tech fields such as aviation, automobile, energy, machinery and other industries. Boron nitride fiber has a variety of excellent properties unique to both boron nitride materials and fiber materials, and has excellent physical and chemical properties such as high temperature resistance, chemical corrosion resistance, good processability, self-lubrication, non-wetting with various metals, small dielectric constant and loss tangent, etc. High-quality BN fiber can be used for a long time in an oxidizing atmosphere below 900°C and an inert atmosphere above 2700°C.
[0003] There are two main methods for preparing boron nitride fibers, one is the inorganic precursor method and the other is the organic precursor method. The boron nitride fibers produced by the inorganic precursor method have high impurity content and poor mechanical properties. The conventional organic precursor method has a complex process, high sintering temperature, and high cost. In addition, neither the inorganic precursor method nor the organic precursor method can make the boron nitride fibers have a certain orientation, resulting in low mechanical properties of the boron nitride fibers. Therefore, it is very necessary to improve the orientation degree of boron nitride fibers.
[0004] Electric field induced crystallization technology can utilize the dielectric properties of the precursor to polarize and move the precursor molecules under the action of the electric field, thereby achieving the purpose of molecular directional arrangement. Slow crystallization technology has the advantages of simple operation, low cost, and less equipment required, and can obtain single crystals with fewer defects and high purity. By combining electric field induced crystallization orientation with slow crystallization technology, highly oriented precursor crystalline fibers can be obtained, and then subsequent calcination can reduce the surface defects of the fibers, and obtain boron nitride fibers with high orientation and good mechanical properties.
[0005] The Chinese patent "A boron nitride fiber and its preparation method" (application number: 202211564168.6, publication number: CN115626829A, publication date: 2023.01.20) discloses a boron nitride fiber and its preparation method. The method melts and draws a boron nitride precursor, then performs a heat treatment in three heating stages, and treats the boron nitride precursor fiber to a fixed length in the second heating stage. The obtained boron nitride fiber has a high degree of orientation and improved mechanical properties. However, the method is complicated to operate, and the temperature range of the three heat treatment stages is difficult to control, which may result in boron nitride fibers with a low degree of orientation and poor mechanical properties.
[0006] The Chinese patent "A boron nitride fiber, its preparation method and application" (application number: 202211598567.4, publication number: CN115611635A, publication date: 2023.03.21) discloses a boron nitride fiber, its preparation method and application. This method winds the boron oxide fiber on the insulating medium of the DBD reactor, and obtains the boron nitride fiber by heating and discharging the DBD reactor. This method reduces the reaction temperature and accelerates the reaction rate, but the orientation degree of the obtained boron nitride fiber is not high.
[0007] Chinese patent "A low-temperature preparation method for BN fibers and BN fibers" (application number: 202310107039.2, publication number: CN 115821428 A, publication date: 2023.03.21) discloses a low-temperature preparation method for BN fibers and BN fibers. The method uses polyborazine as an organic precursor raw material for melt spinning, adds silicone oil to obtain raw fibers, and performs two-stage heating treatment on the pretreated raw fibers to obtain BN fibers. The BN fibers obtained by this method have good crystallization effect, but low degree of orientation.
[0008] The Chinese patent "A chemical cross-linking method for preparing boron nitride fibers by an organic precursor method" (application number: 202310067632.9, publication number: CN116121910A, publication date: 2023.05.16) discloses a chemical cross-linking method for preparing boron nitride fibers by an organic precursor method. The boron nitride precursor fibers are cross-linked and infusible treated in different atmospheres, and then inorganicized and ceramicized to obtain boron nitride fibers. This method improves the cross-linking efficiency and ceramic yield, but the orientation degree of the boron nitride fibers is not high. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing high-crystalline oriented boron nitride fibers, which solves the problems of low orientation degree and poor mechanical properties of boron nitride fibers in the prior art.
[0010] The technical solution adopted by the present invention is:
[0011] A method for preparing high crystalline oriented boron nitride fiber is specifically implemented according to the following steps:
[0012] Step 1, prepare supersaturated precursor solution:
[0013] Boric acid and melamine are weighed in a molar ratio of 3:1, deionized water is added, and the mixture is fully dissolved in a water bath, heated in a water bath, and then the obtained supersaturated solution is poured into a petri dish to obtain a supersaturated precursor solution;
[0014] Step 2, place the single crystal seed crystal:
[0015] The seed crystal size was cut into Φ2.5mm×10mm, and it was polished with sandpaper to remove impurities and oxide layer, then cleaned with acetone and placed horizontally in the center of the culture dish;
[0016] Step 3, electric field induced crystal orientation;
[0017] The culture dish in step 2 is placed in an adjustable electric field device, the seed crystal is parallel to the electric field direction, the supersaturated precursor solution is volatilized slowly at a uniform speed, the crystal fiber is slowly precipitated, and the electric field intensity is controlled to induce fiber orientation crystallization to obtain precursor crystallized fiber;
[0018] Step 4: calcination treatment by electric field regulation:
[0019] The precursor crystalline fiber obtained in step 3 is placed in a heating furnace, electrode plates are added to both sides of the furnace tube, an electric field is applied through the electrode plates, calcined, and kept warm for 2 hours to obtain crystalline oriented boron nitride fiber.
[0020] Furthermore, the concentration of the precursor solution in step 1 is 0.05 mol / L to 0.08 mol / L.
[0021] Furthermore, the water bath heating temperature in step 1 is 90° C. and the heating time is 4 hours.
[0022] Furthermore, the seed crystal in step 2 is a (111) oriented nickel-based single crystal high-temperature alloy.
[0023] Furthermore, the seed crystal is placed in step 3 in a horizontal manner at the center of the bottom of the culture dish, parallel to the direction of the electric field.
[0024] Furthermore, the volatilization rate of the supersaturated precursor solution in step 3 is 6.9 ml / h to 8.3 ml / h.
[0025] Furthermore, the electric field strength in step 3 is 666-1250 V / cm.
[0026] Furthermore, in step 3, the culture dish temperature is 90° C. and the crystallization time is 45 to 60 hours.
[0027] Furthermore, in step 4, the applied electric field strength is 666-1250 V / cm, and the calcination temperature is 1100° C.-1250° C.
[0028] The beneficial effects of the present invention are: a method for preparing high-crystalline oriented boron nitride fibers, which can obtain BN fibers with high orientation and high mechanical properties, and the fiber surface is smooth and the arrangement density is high. Seed crystals are used to provide a "template" for crystal growth to regulate the morphology and size of the crystals. The orderly arrangement of molecules of similar sizes during slow crystallization is fully utilized, so that other molecules with large size differences will not enter the crystal to cause defects, and the obtained fiber size is longer and the purity is higher. When the precursor solution is crystallized, an electric field is applied, and the dielectric properties of the precursor are utilized to polarize and move the precursor molecules under the action of the electric field, thereby achieving the purpose of molecular directional arrangement. In the subsequent calcination stage, a small amount of defects such as cracks and holes on the surface of the precursor fiber will gradually heal under the action of in-situ hot stretching, and the application of an electric field during calcination also maintains the fiber orientation. The boron nitride fiber finally obtained has a high degree of orientation and good mechanical properties, and has broad application prospects in the fields of aerospace, metallurgy, nuclear industry, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the adjustable electric field device of the present invention. DETAILED DESCRIPTION
[0030] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] A method for preparing high crystalline oriented boron nitride fiber is specifically implemented according to the following steps:
[0032] Step 1, prepare supersaturated precursor solution:
[0033] Boric acid and melamine were weighed in a molar ratio of 3:1, and deionized water was added to control the solution concentration to 0.05 mol / L to 0.08 mol / L, and the solution was fully dissolved under water bath heating conditions. The water bath was heated at 90°C for 4 hours, and then the obtained supersaturated solution was poured into a petri dish to obtain a supersaturated precursor solution.
[0034] Step 2, place the single crystal seed crystal:
[0035] A (111) oriented nickel-based single crystal high-temperature alloy was selected as the seed crystal, cut into a size of Φ2.5 mm×10 mm, polished with sandpaper to remove impurities and oxide layer, and then cleaned with acetone and placed horizontally in the center of the culture dish, parallel to the direction of the electric field.
[0036] Step 3, electric field induced crystal orientation:
[0037] Place the culture dish from step 2 in Figure 1In the adjustable electric field device shown, the negative electrode of the electrode plate is fixed, and the positive electrode can be adjusted at an adjustable distance to adjust the electric field strength. The direction of the electric field is from left to right. The culture dish is placed in the center of the electric field. The solvent evaporation rate is controlled to be 6.9 ml / h to 8.3 ml / h, so that the precursor solution evaporates slowly and uniformly, and the crystal fibers precipitate slowly. The electric field strength is controlled to be 666 to 1250 V / cm to induce fiber orientation crystallization. The culture dish temperature is set to 90°C, and the crystallization time is 45 to 60 hours to obtain precursor crystalline fibers.
[0038] Step 4: calcination treatment by electric field regulation:
[0039] Place the precursor crystalline fiber obtained in step 3 into a heating furnace, add electrode plates on both sides of the furnace tube, apply an electric field through the electrode plates, the electric field strength is 666-1250V / cm, the calcination temperature is 1100℃-1250℃, keep warm for 2h, and obtain crystalline oriented boron nitride fiber.
[0040] The invention provides a "template" for crystal growth by adding seed crystals, reduces the potential barrier that must be overcome when transforming into crystals, and uses seed crystals to regulate the shape and size of crystals; controls the concentration of the precursor solution to be 0.05 mol / L-0.08 mol / L, so that the molecular sizes in the precursor solution are similar, and slow crystallization is better performed; controls the solvent evaporation rate to be 6.9 ml / h-8.3 ml / h, so that the crystal precipitation rate and solubility are kept in dynamic balance, and the solubility is kept constant at all times, so that the precursor crystal fiber has fewer defects and higher fiber density, and the purity of the fiber can also be improved, and impurities in the fiber can be reduced; controls the electric field strength to be 666-1250 V / cm, and utilizes the dielectric properties of the precursor to polarize and move the precursor particles under the action of the electric field, so that the particles are oriented, and the oriented arrangement of the crystal fiber removes the grain boundary that is easy to generate crack sources. By controlling the calcination temperature to 1100-1250°C, a small amount of defects on the surface of the precursor fiber are healed under the action of in-situ hot stretching. The electric field strength applied during calcination is controlled to 666-1250V / cm to maintain the fiber orientation during the sintering process. Since the orientation degree of the final fiber is improved, the mechanical properties are greatly improved.
[0041] The present invention prepares a highly oriented boron nitride fiber by electric field induced crystal orientation. The seed crystal provides a "template" for crystal growth, and can also regulate the crystal morphology and size. The orderly arrangement of particles of similar sizes during the slow crystallization of the precursor is fully utilized to exclude other molecules with large size differences, thereby more effectively reducing crystal defects. The solvent evaporation rate maintains a dynamic balance between the crystal precipitation speed and solubility, thereby ensuring the smooth progress of the slow crystallization. The application of an electric field causes the precursor particles to be polarized and move under the action of the electric field, thereby achieving the purpose of directional arrangement of the particles. During the calcination stage, a small amount of defects such as cracks and holes on the surface of the precursor fiber will gradually heal under the action of in-situ thermal stretching. At the same time, the application of an electric field during calcination also maintains the fiber orientation. The finally obtained crystalline oriented boron nitride fiber is highly oriented, has a smooth surface, has fewer defects, and has improved mechanical properties. It has broad application prospects in the fields of aerospace, metallurgy, and nuclear industry.
[0042] Example 1
[0043] First, weigh boric acid and melamine in a molar ratio of 1:3, 4.635g of boric acid and 3.155g of melamine, then add 500ml of deionized water, control the solution concentration to 0.05mol / L, heat in a water bath to fully dissolve it, the water bath heating temperature is 90℃, the heating time is 4h, pour into a petri dish, and obtain a supersaturated precursor solution;
[0044] A (111) oriented nickel-based single crystal high-temperature alloy with a size of Φ2.5mm×10mm was used as a seed crystal and placed horizontally at the center of the bottom of the culture dish, parallel to the direction of the electric field;
[0045] The culture dish was placed in an adjustable electric field device, the solvent evaporation rate was adjusted to 8.3 ml / h, the electric field strength was adjusted to 1250 V / cm, and the temperature of the heating plate below the culture dish was set to 90°C. The crystallization time was 60 hours to obtain the precursor crystalline fiber;
[0046] The obtained precursor crystalline fiber was calcined at a temperature of 1250° C., a holding time of 2 h, and an electric field strength of 1250 V / cm to obtain a crystalline oriented boron nitride fiber.
[0047] Table 1 is a comparison of the average single-filament tensile strength, orientation degree and fiber morphology of the electric field induced crystallization oriented BN fiber, the melt drawing precursor BN fiber and the conventional BN fiber in Example 1.
[0048] Table 1
[0049]
[0050] As can be seen from Table 1, the tensile strength of conventional BN fibers is the smallest, followed by melt-drawn precursor BN fibers. The tensile strength of the highly oriented BN fibers in Example 1 is the largest, which is closely related to their respective orientations. Conventional BN fibers are composed of a chaotic layer structure, with disorder between layers and almost no orientation. The melt-drawn precursor BN fibers use the cohesive force generated by thermal sintering shrinkage as a source of tension, and in situ change the fiber microstructure to promote fiber crystallization orientation. However, due to the difficulty in determining the temperature range, the obtained BN fibers will also have low orientation and poor mechanical properties. In Example 1, by adding highly oriented seed crystals, the crystals grow along the orientation of the seed crystals, and by slow crystallization, the internal defects of the fibers are reduced. By using the dielectric properties of the precursor, an electric field is applied to orient the precursor, and the orientation degree of the resulting BN fibers is also greatly improved. The subsequent calcination operation also reduces the surface defects of the fibers, making the fiber surface smooth, and the application of the electric field during calcination also ensures the fiber orientation, and the mechanical properties are improved.
[0051] Example 2
[0052] First, weigh boric acid and melamine in a molar ratio of 1:3, 4.635g of boric acid and 3.155g of melamine, then add 416ml of deionized water, control the solution concentration to 0.06mol / L, heat in a water bath to fully dissolve it, the water bath heating temperature is 90℃, the heating time is 4h, pour into a petri dish, and obtain a supersaturated precursor solution;
[0053] A (111) oriented nickel-based single crystal high-temperature alloy with a size of Φ2.5mm×10mm was used as a seed crystal and placed horizontally at the center of the bottom of the culture dish, parallel to the direction of the electric field;
[0054] The culture dish was placed in an adjustable electric field device, the solvent evaporation rate was adjusted to 7.5 ml / h, the electric field strength was adjusted to 1000 V / cm, and the temperature of the heating plate below the culture dish was set to 90°C. The crystallization time was 55 h, and the precursor crystalline fiber was obtained;
[0055] The obtained precursor crystalline fiber was calcined at a temperature of 1200° C., a holding time of 2 h, and an electric field strength of 1000 V / cm to obtain a crystalline oriented boron nitride fiber.
[0056] Example 3
[0057] First, weigh boric acid and melamine in a molar ratio of 1:3, 4.635g of boric acid and 3.155g of melamine, then add 357ml of deionized water, control the solution concentration to 0.07mol / L, heat in a water bath to fully dissolve it, the water bath heating temperature is 90℃, the heating time is 4h, pour into a petri dish, and obtain a supersaturated precursor solution;
[0058] A (111) oriented nickel-based single crystal high-temperature alloy with a size of Φ2.5mm×10mm was used as a seed crystal and placed horizontally at the center of the bottom of the culture dish, parallel to the direction of the electric field;
[0059] The culture dish was placed in an adjustable electric field device, the solvent evaporation rate was adjusted to 7.1 ml / h, the electric field strength was adjusted to 800 V / cm, and the temperature of the heating plate below the culture dish was set to 90°C. The crystallization time was 50 h, and the precursor crystalline fiber was obtained;
[0060] The obtained precursor crystalline fiber was calcined at a temperature of 1150° C., a holding time of 2 h, and an electric field strength of 800 V / cm to obtain a crystalline oriented boron nitride fiber.
[0061] Example 4
[0062] First, weigh boric acid and melamine in a molar ratio of 1:3, 4.635g of boric acid and 3.155g of melamine, then add 312ml of deionized water, control the solution concentration to 0.08mol / L, heat in a water bath to fully dissolve it, the water bath heating temperature is 90℃, the heating time is 4h, pour into a petri dish, and obtain a supersaturated precursor solution;
[0063] A (111) oriented nickel-based single crystal high-temperature alloy with a size of Φ2.5mm×10mm was used as a seed crystal and placed horizontally at the center of the bottom of the culture dish, parallel to the direction of the electric field;
[0064] The culture dish was placed in an adjustable electric field device, the solvent evaporation rate was adjusted to 6.9 ml / h, the electric field strength was adjusted to 666 V / cm, and the temperature of the heating plate below the culture dish was set to 90°C. The crystallization time was 45 h, and the precursor crystalline fiber was obtained;
[0065] The obtained precursor crystalline fiber was calcined at a temperature of 1100° C., a holding time of 2 h, and an electric field strength of 666 V / cm to obtain a crystalline oriented boron nitride fiber.
[0066] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing high crystalline oriented boron nitride fiber, characterized in that: Please follow the steps below to implement: Step 1, prepare supersaturated precursor solution: Boric acid and melamine are weighed in a molar ratio of 3:1, deionized water is added, and the mixture is fully dissolved in a water bath, heated in a water bath, and then the obtained supersaturated solution is poured into a petri dish to obtain a supersaturated precursor solution; Step 2, place the single crystal seed crystal: The seed crystal size was cut into Φ2.5mm×10mm, and it was polished with sandpaper to remove impurities and oxide layer, then cleaned with acetone and placed horizontally in the center of the culture dish; Step 3, electric field induced crystal orientation; The culture dish in step 2 is placed in an adjustable electric field device, the seed crystal is parallel to the electric field direction, the supersaturated precursor solution is volatilized slowly at a uniform speed, the crystal fiber is slowly precipitated, and the electric field intensity is controlled to induce fiber orientation crystallization to obtain precursor crystallized fiber; Step 4: calcination treatment by electric field regulation: The precursor crystalline fiber obtained in step 3 is placed in a heating furnace, electrode plates are added to both sides of the furnace tube, an electric field is applied through the electrode plates, calcined, and kept warm for 2 hours to obtain crystalline oriented boron nitride fiber.
2. The method for preparing a highly crystalline oriented boron nitride fiber according to claim 1, characterized in that: The concentration of the precursor solution in step 1 is 0.05 mol / L to 0.08 mol / L.
3. The method for preparing a highly crystalline oriented boron nitride fiber according to claim 1, characterized in that: The water bath heating temperature in step 1 is 90° C. and the heating time is 4 h.
4. The method for preparing a high crystalline oriented boron nitride fiber according to claim 1, characterized in that: The seed crystal in step 2 is a (111) oriented nickel-based single crystal high-temperature alloy.
5. The method for preparing a highly crystalline oriented boron nitride fiber according to claim 1, characterized in that: The seed crystal is placed in step 3 horizontally at the center of the bottom of the culture dish, parallel to the direction of the electric field.
6. The method for preparing a highly crystalline oriented boron nitride fiber according to claim 1, characterized in that: The volatilization rate of the supersaturated precursor solution in step 3 is 6.9 ml / h to 8.3 ml / h.
7. The method for preparing a highly crystalline oriented boron nitride fiber according to claim 1, characterized in that: The electric field strength in step 3 is 666-1250 V / cm.
8. The method for preparing a highly crystalline oriented boron nitride fiber according to claim 1, characterized in that: In step 3, the culture dish temperature is 90° C. and the crystallization time is 45 to 60 hours.
9. The method for preparing a high crystalline oriented boron nitride fiber according to claim 1, characterized in that: In step 4, the applied electric field strength is 666-1250 V / cm, and the calcination temperature is 1100° C.-1250° C.
Citation Information
Patent Citations
Boron nitride fiber and preparation method and application thereof
CN115611635A
Boron nitride fiber and preparation method thereof
CN115626829A
Low-temperature preparation method of BN fiber and BN fiber
CN115821428A
A low-temperature preparation method for BN fibers and BN fibers
CN115821428B
Chemical crosslinking method suitable for preparing boron nitride fiber by organic precursor method
CN116121910A